Case report: ETS1 gene deletion associated with a low number of recent thymic emigrants in three patients with Jacobsen syndrome - Trachsel, Tina; Prader, Seraina; Steindl, Katharina; Pachlopnik Schmid, Jana (Frontiers in Immunology, 2022)
Jacobsen syndrome is a rare genetic disorder associated with a terminal deletion in chromosome 11. The clinical presentation is variable. Although immunodeficiency has been described in patients with Jacobsen syndrome, a clear genotype-phenotype correlation has not yet been established. Here, we report on the immunologic phenotypes of four patients with Jacobsen syndrome. All four patients showed one or more atypical immunologic features. One patient suffered from recurrent viral infections, two patients had experienced a severe bacterial infection and one had received antibiotic prophylaxis since early childhood. One patient had experienced severe, transient immune dysregulation. Hypogammaglobulinemia and low B cell counts were found in two patients, while the number of recent thymic emigrants (CD31+CD45RA+ CD4 cells) was abnormally low in three. When considering the six immune-related genes located within the affected part of chromosome 11 (ETS1, TIRAP, FLI1, NFRKB, THYN1, and SNX19), only the ETS1 gene was found be deleted in the three patients with low numbers of recent thymic emigrants and non-switched memory B cells. Our findings support the hypothesis whereby Jacobsen syndrome is associated with a combined immunodeficiency with variable presentation. Further investigations of potential genotype-phenotype correlations are warranted and might help to personalize patient management in individuals lacking immune-related genes. In addition, we recommend immunologic follow-up for all patients with Jacobsen syndrome, as immune abnormalities may develop over time.